Metastatic bone disease: Pathogenesis and therapeutic options - Stella D'Oronzo; Robert Coleman; Janet Brown; Francesco Silvestris (Journal of Bone Oncology, 2019)
Bone metastases (BM) are a common complication of cancer, whose management often requires a multidisciplinary approach. Despite the recent therapeutic advances, patients with BM may still experience skeletal-related events and symptomatic skeletal events, with detrimental impact on quality of life and survival.A deeper knowledge of the mechanisms underlying the onset of lytic and sclerotic BM has been acquired in the last decades, leading to the development of bone-targeting agents (BTA), mainly represented by anti-resorptive drugs and bone-seeking radiopharmaceuticals. Recent pre-clinical and clinical studies have showed promising effects of novel agents, whose safety and efficacy need to be confirmed by prospective clinical trials.Among BTA, adjuvant bisphosphonates have also been shown to reduce the risk of BM in selected breast cancer patients, but failed to reduce the incidence of BM from lung and prostate cancer. Moreover, adjuvant denosumab did not improve BM free survival in patients with breast cancer, suggesting the need for further investigation to clarify BTA role in early-stage malignancies.The aim of this review is to describe BM pathogenesis and current treatment options in different clinical settings, as well as to explore the mechanism of action of novel potential therapeutic agents for which further investigation is needed. Keywords: Bone metastases, Osteotropic tumors, Skeletal related events, Bone targeting agents